The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/2325967120930829
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport After Anterior Cruciate Ligament Injury: Panther Symposium ACL Injury Return to Sport Consensus Group

Abstract: Background: A precise and consistent definition of return to sport (RTS) after anterior cruciate ligament (ACL) injury is lacking, and there is controversy surrounding the process of returning patients to sport and their previous activity level. Purpose: The aim of the Panther Symposium ACL Injury Return to Sport Consensus Group was to provide a clear definition of RTS after ACL injury and a description of the RTS continuum as well as provide clinical guidance on RTS testing and decision-making. Study Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 81 publications
1
26
0
1
Order By: Relevance
“…The patients who want to return to training and next to return to dynamic sport the supervised physiotherapy (SP) should continue for at least six or more months [13,14]. The final decision to return the patient to sports activity should be based on a clinical examination, an assessment of the restored functions of the joint and the whole body, and the patient's mental readiness [15]. Czuppon et al (2014) suggested that variables associated with a return to sports after ACLR included higher quadriceps strength, less effusion, less pain, greater tibial rotation, higher activity score, higher athletic confidence, higher preoperative knee selfefficacy, lower kinesiophobia, and higher preoperative self-motivation [16].…”
Section: Introductionmentioning
confidence: 99%
“…The patients who want to return to training and next to return to dynamic sport the supervised physiotherapy (SP) should continue for at least six or more months [13,14]. The final decision to return the patient to sports activity should be based on a clinical examination, an assessment of the restored functions of the joint and the whole body, and the patient's mental readiness [15]. Czuppon et al (2014) suggested that variables associated with a return to sports after ACLR included higher quadriceps strength, less effusion, less pain, greater tibial rotation, higher activity score, higher athletic confidence, higher preoperative knee selfefficacy, lower kinesiophobia, and higher preoperative self-motivation [16].…”
Section: Introductionmentioning
confidence: 99%
“…These negative feelings and psychological aspects may play an important role for recovery and psychological factors may predict outcomes after an ACL-R [ 33 ]. Even though a recent consensus statement article concludes that psychological factors play an important role in return to sport, it remains unclear if psychological scales can be used to capture this and improve the rehabilitation process [ 34 ]. Thereto, a study by Piussi et al 2021 suggested that physiotherapists express insufficient knowledge of how to address psychological impairments during rehabilitation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 Between 21% and 37% of NFL athletes who suffer an ACL injury never appear in another NFL game. 2,16 Those who do RTP have been shown to perform at a lower level on average than they did before injury. 2 The physical demands imposed on NFL athletes predispose them to greater injury risk in comparison to the general population.…”
Section: Discussionmentioning
confidence: 99%